Faktor Risiko Pola Asuh Orang Tua terhadap Gaming Disorder pada Remaja - Pambudi, Tesalonika Arina; Rachmayanti, Riris Diana (Fakultas Kedokteran, Universitas Andalas, 2024)
Gaming disorder is often found among children and adolescents. This disorder of self-control over games that cause addiction is defined by WHO as a behavioral disorder. Risk factors for gaming disorder come from internal factors and external factors. One of the significant external risk factors is parents' parenting style towards their children. Objective: To explored and analyze external risk factors for gaming disorders in adolescents related to parental parenting patterns. Methods: The research method used is qualitative with a phenomenological approach using purposive and in-depth interview techniques. There were 12 informants, 8 of whom were primary informants and 4 of whom were key informants. The main informant was an adolescent mobile legends game player in Surabaya who was diagnosed with gaming disorder based on the results of a preliminary study using the gaming disorder instrument from the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Results: parenting patterns at risk are parenting patterns that pamper children, parenting patterns that lack control over parents, and parenting patterns that are indifferent and harsh.Conclusion: Ineffective parenting has an impact on teenagers' self-control, which has the potential to cause teenagers to fall into gaming addiction or gaming disorder.Keywords: adolescents, gaming disorder, parenting style